Economic zones and local income inequality: Evidence from Indonesia - Cecília Hornok; Dewa Gede Sidan Raeskyesa (The Journal of Economic Inequality, 2023)
Economic zones can be powerful drivers of economic growth in developing countries. However, less is known about their distributional impact on the local society. This paper provides empirical evidence from Indonesian provinces on the relationship between economic zones and within-province income inequality. We apply fixed-effects panel estimation to province-level data for the whole of Indonesia, which we then complement with separate studies on the opening of three economic zones in three provinces using the synthetic control method. The results suggest that the above relationship is positive overall. The estimated rise in income inequality after a zone opens is, however, relatively small on average and may be short-lived. Moreover, the average estimate masks large regional differences, which suggests that the inequality implications of economic zone policies depend on local conditions. One possible explanation for the rise in inequality is that the unskilled population benefits disproportionately less from the policy.
Keywords: D31; F63; O15; O25; 330; Economic zones; Income distribution; Indonesia; Place-based policy; Synthetic control method